DIVERSI BAGI ANAK YANG BERHADAPAN DENGAN HUKUM DI KABUPATEN TANA TORAJA - Christian A Caesar (Paulus Law Journal, 2021)
Diversion is the settlement of juvenile cases that have been transferred from the criminal justice process to the non-criminal justice process. This is because the child is the party who has not been able to legally account for his dressing. The purpose of the research was to analyse in depth the background execution of the diversion of the dealing with the law and the obstacles affecting the implementation of diversion. This research uses a type of normative empirical legal research by finding the empirical in the field that concerns the problems of primary that is obtained directly from the results of the interviews with respondents and interviewees as well as data secondary data is obtained through literature-literature which deals directly with the issue discussed in this study. The research results give a hint that execution is a form of diversion pemidanaan the more education against children as well as the factors that influence the implementation of restorative justice in the diversion on the criminal justice system, child is a factor the substance of the law, human resource law enforcement officers who have yet to grasp the versioned, support and cooperation among related agencies not optimal, and are also victims/families of the victims have not been able to receive them well on diversion.